Tunable Photoluminescence Properties of Cotton Fiber With Gradually Changing Crystallinity - Zhou, Qing; Liu, Man; Li, Chuchu; Lu, Shijia; Lei, Bin; Jiang, Jiantang; Yin, Ying; Zhang, Yuanchao; Shen, Yifeng (Frontiers in Chemistry, 2022)
The alkali mercerizing process of semicrystalline cotton fiber (CF) is widely used in the printing and dyeing industry. The crystallinity change in the mercerizing process have been studied and certain laws have been obtained, but there is still a certain distance between the theoretical research results and the practical application. CF is almost composed of cellulose, combined with the photoluminescence (PL) phenomenon of cellulose, herein, the varying crystallinity is correlated with its PL behavior after being treated with different concentrations of NaOH. In line with the characteristics of nonconventional luminogens, CF enjoy excitation-dependent emission and persistent room temperature phosphorescence (p-RTP) behavior. The emission spectra of all samples under the same excitation wavelength indicates that the change of CF crystallinity has a significant impact on its fluorescence and p-RTP emission. As the concentration of NaOH increases, the varying trend of quantum efficiency (QY) is consistent with the changed crystallinity of CF. Interestingly, the lifetime of p-RTP is exactly the opposite of the crystallinity change law. Clustering-triggered emission (CTE), crystallization-Induced Phosphorescence (CIP) mechanism and the swelling due to hydrated sodium ions can reasonably explain these interesting photophysical processes, which also can be supported by theoretical calculations. The above studies have basically clarified the inherent law between the crystalline change of CF and the PL emission behavior during the alkali treatment process, which can be used as a theoretical reference for real-time monitoring of CF crystallinity changes using the spectral method in the actual cotton mercerizing process.